A feasibility and safety study of concurrent chemotherapy based on genetic testing in patients with high-risk salivary gland tumors: Preliminary results. Issue 17 (April 2018) - Li, Rongrong; Dou, Shengjin; Ruan, Min; Zhang, Chenping; Zhu, Guopei
Abstract: Background: This prospective study was conducted to evaluate the feasibility and safety of customized chemotherapy regimens based on the gene characteristics of salivary gland tumors. Methods: Patients were enrolled with histologically confirmed intermediate or high grade, stage T3–4, N1–3 disease, and T1–2, N0 patients with a close (⩽1 mm) or microscopically positive surgical margin were also enrolled in the study. All patients received radical surgery and postoperative concurrent chemoradiotherapy. To evaluate the responsiveness of therapies, the chemotherapy regimen was based on gene targets, β-tubulin III, ABCB1, STMN1, and CYP1B1 (for docetaxel) and TYMS (for pemetrexed). The primary endpoints were treatment compliance and acute toxicities. Results: A total of 20 patients were enrolled between September 2013 and January 2016. The median age was 46 years (range: 23–70 years). Genetic testing showed that 8 patients may have been sensitive to docetaxel, 5 patients may have been sensitive to pemetrexed, and 7 patients sensitive to either docetaxel or pemetrexed. All patients received the full dose of radiation. A total of 19 patients (95%) completed 2 cycles of concurrent chemotherapy (CCT). One patient treated concurrently with pemetrexed experienced grade 3 neutropenia. Three patients experienced grade 3 oral mucositis, and 2 patients experienced grade 3 dermatitis. Conclusion: Our study demonstrated that a CCT selecting method based on the gene targets associated with drug sensitivity was clinically feasible and safe. Further studies enrolled more patients with longer follow-up times are needed to confirm the clinical efficacy of this CCT selecting method.